DEQOREL: An Intelligent Service Robot to Improve Restaurant Service Efficiency - Qori Anjelika, Dea; Leni, Desmarita; Muchlisinalahuddin (Universitas Negeri Padang, 2025)
Cafes have become a favorite place for various groups by providing a variety of food and drinks. However, challenges such as worker fatigue and human error often interfere with service. To overcome these problems, this research developed an intelligent waiter robot named Deqorel. Deqorel is designed to improve restaurant service efficiency through trajectory sensor-based automatic navigation and optimization algorithms. Deqorel is equipped with a 15-inch interactive screen, an energy-efficient DC motor, and a lithium-ion battery that supports operations for long periods of time. The robot frame uses 304 stainless steel with stress calculations to ensure strength and safety. The results show that Deqorel is able to provide accurate, fast, and responsive service in a dynamic restaurant environment, thereby increasing customer satisfaction as well as restaurant productivity.